2020
DOI: 10.1148/rg.2020190058
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Diffusion-Tensor Imaging Acquisition for Spinal Cord Assessment: Physical Basis and Technical Adjustments

Abstract: Diffusion-tensor imaging (DTI) has been used in the assessment of the central nervous system for the past 3 decades and has demonstrated great utility for the functional assessment of normal and pathologic white matter. Recent technical advances have permitted the expansion of DTI applications to the spinal cord. MRI of the spinal cord has traditionally been limited to conventional sequences, which provide information regarding changes in the anatomic shape of a structure or its signal intensity, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…This study shows that the DTI parameters FA, FT, FTR1, and FTR2 of patients with high cervical spinal cord tumor are lower than those of healthy volunteers, and the ADC is higher than that of healthy volunteers, which is basically consistent with previous studies [ 16 ]. Considering the compression of spinal cord or tumor infiltration, the structure of white matter fiber bundle is significantly affected, and the degree of anisotropy is also changed [ 17 ]. In this study, the DTI parameters of the upper layer, the lower layer, and the control group were compared, respectively, and it was found that the differences of FA, ADC, FT, and FTR mainly existed in the lower layer and the upper layer of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that the DTI parameters FA, FT, FTR1, and FTR2 of patients with high cervical spinal cord tumor are lower than those of healthy volunteers, and the ADC is higher than that of healthy volunteers, which is basically consistent with previous studies [ 16 ]. Considering the compression of spinal cord or tumor infiltration, the structure of white matter fiber bundle is significantly affected, and the degree of anisotropy is also changed [ 17 ]. In this study, the DTI parameters of the upper layer, the lower layer, and the control group were compared, respectively, and it was found that the differences of FA, ADC, FT, and FTR mainly existed in the lower layer and the upper layer of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…This may be influenced by the difficulty in analyzing postoperative DTI. Metallic implants located within Sensory Light touch 0.035 -0.334 -0.366 -0.174 0.016 -0.211 0.407 0.344 0.265 -0.006 0.095 0.116 0.198 0.044 0.054 0.142 0.059 0.123 Pinprick -0.006 -0.391 -0.469 -0.253 -0.012 -0.126 0.295 0.228 0.156 0.000 -0.027 -0.027 0.059 -0.095 0.024 0.020 -0.032 0.071 Total -0.006 -0.391 -0.469 -0.253 -0.012 -0.126 0.295 0.228 0.156 0.000 -0.027 -0.027 0.059 -0.095 0.024 0.020 -0.032 0.071 www.e-arm.org the spine can cause geometric distortions that may cause inaccuracies in the measurement of DTI parameters and tractography [15]. This was also demonstrated in our study, wherein the failure rate of DTI analysis was more than doubled after surgery than before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The structural connectivity network defines the association between different areas of the CNS, but cannot determine the direction, nor distinguish between excitatory or inhibitory connections (11, 12). It can be evaluated with diffusion imaging tractography (DIT), combining diffusion magnetic resonance imaging (MRI), such as diffusion tensor imaging, with the visual representation of nerve tracts by tractography or using tract atlases (12)(13)(14). This technique focuses more on tracing white matter connections but mapping disconnections between gray matter regions due to focal lesions is possible (12).…”
Section: Assessment Of the Spasticity-plus Syndrome With Imagingmentioning
confidence: 99%
“…Most MS imaging studies focus on the brain to illustrate motor, sensitive, and cognitive impairment, even if some symptoms involve the spinal cord, such as spasticity. This is partly due to the challenging imaging of the spinal cord, since its axons have a small diameter and it is susceptible to motion artifacts (e.g., body fluid pulsation, breathing, and swallowing) (13,14). Therefore, its imaging studies usually involve part of the spinal cord at high spatial resolution, then uses it as a proxy for its entirety (18).…”
Section: Assessment Of the Spasticity-plus Syndrome With Imagingmentioning
confidence: 99%